Bulletin du comité national Olympique de la République Démocratique Allemande (Fiep Bulletin - online, 2015)
Our life is characterized by steadily increasing industrialization and automation of the production processes. Technical progress is felt not only in the sphere of vocational life but also in private life. In the house, too, machines play an ever increasing part; radio and television lead people to experience culture only passively; means of transport decrease to a minimum the time needed to get to work and for long journeys.